Modulation of test anxiety-induced salivary protein secretion by ovarian steroid hormones: a preliminary study - Lorenzo Zallocco; Maurizio Ronci; Andrea Pantalone; Maria Rosa Mazzoni; Eleonora Ramoretti; Antonio Lucacchini; Laura Giusti; Laura Sebastiani (Journal of Physiology and Biochemistry, 2025)
In women the menstrual cycle influences mood and anxiety. Aim of this study was to preliminarily investigate whether different ovarian steroid hormone levels may modulate the psychophysiological responses elicited by test anxiety. Specifically, we compared the secretion of anxiety-induced salivary proteins of healthy women in the early follicular (Pre-Ov group) (low ovarian steroid hormones levels) and mid-luteal (Post-Ov group) (medium/high ovarian steroid hormones levels) phase of the menstrual cycle, during the simulation of an oral examination. Saliva samples were collected before and after a relaxation period and at two post-simulation times and analyzed by two-dimensional electrophoresis and western blot. Proteins corresponding to spots differentially expressed in the two groups across the session were identified through mass spectrometry and most of them corresponded to acute stress and/or oral mucosa immunity biomarkers. The task induced an increase in alpha-amylase, carbonic anhydrase and cystatin S, and a decrease in immunoglobulin light/J chains in both groups. Analogous changes in these proteins have previously been linked to psychological or physical stress. However, specific spots corresponding, for example, to cystatins and 14-3-3 protein, changed exclusively in the Pre-Ov group, while prolactin-inducible protein, polymeric immunoglobulin receptor, fragments of alpha-amylase and immunoglobulins only in the Post-Ov group, indicating a potential modulation of their secretion by ovarian steroid hormones. Overall, the results provide preliminary evidence that ovarian steroid hormones may be a driving factor for differences in physiological responses induced by test anxiety. The results are promising, but further validation in a larger sample is needed.

Effect of prenatal phthalate exposure on fetal development and maternal/neonatal health consequences: A systematic review - Laura Almeida-Toledano; Elisabet Navarro-Tapia; Giorgia Sebastiani; Sílvia Ferrero-Martínez; Patricia Ferrer-Aguilar; Óscar García-Algar; Vicente Andreu-Fernández; María Dolores Gómez-Roig (Science of The Total Environment, 2024)

The relationship between 11 different polygenic longevity scores, parental lifespan, and disease diagnosis in the UK Biobank - Janith Don; Andrew J. Schork; Gwênlyn Glusman; Noa Rappaport; Steve R. Cummings; David Duggan; Anish Raju; Kajsa-Lotta Georgii Hellberg; Sophia Gunn; Stefano Monti; Thomas Perls; Jodi Lapidus; et al. (GeroScience, 2024)
Large-scale genome-wide association studies (GWAS) strongly suggest that most traits and diseases have a polygenic component. This observation has motivated the development of disease-specific “polygenic scores (PGS)” that are weighted sums of the effects of disease-associated variants identified from GWAS that correlate with an individual’s likelihood of expressing a specific phenotype. Although most GWAS have been pursued on disease traits, leading to the creation of refined “Polygenic Risk Scores” (PRS) that quantify risk to diseases, many GWAS have also been pursued on extreme human longevity, general fitness, health span, and other health-positive traits. These GWAS have discovered many genetic variants seemingly protective from disease and are often different from disease-associated variants (i.e., they are not just alternative alleles at disease-associated loci) and suggest that many health-positive traits also have a polygenic basis. This observation has led to an interest in “polygenic longevity scores (PLS)” that quantify the “risk” or genetic predisposition of an individual towards health. We derived 11 different PLS from 4 different available GWAS on lifespan and then investigated the properties of these PLS using data from the UK Biobank (UKB). Tests of association between the PLS and population structure, parental lifespan, and several cancerous and non-cancerous diseases, including death from COVID-19, were performed. Based on the results of our analyses, we argue that PLS are made up of variants not only robustly associated with parental lifespan, but that also contribute to the genetic architecture of disease susceptibility, morbidity, and mortality.

Association of hypnotizability and deep sleep: any role for interoceptive sensibility? - Francesca Diolaiuti; Maria Paola Tramonti Fantozzi; Marco Di Galante; Paola D’Ascanio; Ugo Faraguna; Laura Sebastiani; Enrica L. Santarcangelo (Experimental Brain Research, 2020)

Osmotic adjustments support growth of poplar cultured cells under high concentrations of carbohydrates - Silvia Traversari; Anna De Carlo; Maria Laura Traversi; Antonio Minnocci; Alessandra Francini; Luca Sebastiani; Alessio Giovannelli (Plant Cell Reports, 2020)

Correction to: The Novel C5aR Antagonist DF3016A Protects Neurons Against Ischemic Neuroinflammatory Injury - Laura Brandolini; Marta Grannonico; Gianluca Bianchini; Alessia Colanardi; Pierluigi Sebastiani; Antonella Paladini; Alba Piroli; Marcello Allegretti; Giustino Varrassi; Silvia Di Loreto (Neurotoxicity Research, 2019)

The Novel C5aR Antagonist DF3016A Protects Neurons Against Ischemic Neuroinflammatory Injury - Laura Brandolini; Marta Grannonico; Gianluca Bianchini; Alessia Colanardi; Pierluigi Sebastiani; Antonella Paladini; Alba Piroli; Marcello Allegretti; Giustino Varrassi; Silvia Di Loreto (Neurotoxicity Research, 2019)

Brain Responses to Emotional Stimuli During Breath Holding and Hypoxia: An Approach Based on the Independent Component Analysis - Danilo Menicucci; Fiorenzo Artoni; Remo Bedini; Alessandro Pingitore; Mirko Passera; Alberto Landi; Antonio L’Abbate; Laura Sebastiani; Angelo Gemignani (Brain Topography, 2014)

Medial prefrontal cortex early lesion effects on classical conditioned bradycardia - Laura Sebastiani; Brunello Ghelarducci (Experimental Brain Research, 2002)